Feasibility Study of Coffee Shop Business in Lidah Wetan, Lakarsantri District, Surabaya City - Naufal Dzaki Abdullah; Siti Mujannah; Achmad Yanu Alif Fianto (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to analyze the feasibility of a coffee shop business in Lidah Wetan, Lakarsantri District, Surabaya City. The method used is a case study with a qualitative approach, which focuses on the analysis of three main feasibility indicators: Revenue Cost Ratio (R/C Ratio), Benefit Cost Ratio (B/C Ratio), and Return On Investment (ROI). Data were collected through observation, interviews, and documentation studies from six coffee shops as samples. The results of the study indicate that all business units analyzed are declared feasible to run. This is evidenced by the value of the three financial ratios which are consistently above the feasibility threshold (>1). The average R/C Ratio of 3.98 indicates that every Rp1 of costs incurred generates revenue of Rp3.98. The average B/C Ratio of 2.98 indicates that every Rp1 of costs generates a net profit of Rp2.98. Meanwhile, the average ROI of 2.98% proves that the investment made provides a positive return.